Regla de la cadena

Si y es una función de u, y u es una función de x, entonces
Por ejemplo:
y= (x2+1)5
y= u5

u= x2+1

y´=5u4

u´= 2x

y´= 5u4*2x
y´= 5(x2+1)4 2x
y´= 10x(x2+1)4

y= (3x+1)6
u= 3x+1

u´=3

v= u6

v´= 6u5

= 6u5*3
 = 18(3x+1)5

y= (3x2+6)1/2
u= 3x2+6

u´=6x

y= u1/2

y´= 1/2u ½ = 1/ 2u ½

y´= 6x/2u1/2
y´=3x/(3x2+6)1/2

Si y= [u(x)]n entonces y´=n[u(x)]n-1 * du/dx

=

*

y=(4x+3)7
y´=7(4x+3)6*4
y´=28(4x+3)6

y=

=(3x+ ) -3/4

=

y´=-3/4(3x+1/2)-7/4*3
y´=-9/4(3x+1/2)-7/4
y´= -

/

/

y´=  

 

y=
u= x-1

u´=1

v= x+1

v´=1

y´= 3

y´=

 

 

y´=

y´=
y´=

*

=

=

 

 

 

Sign up to vote on this title
UsefulNot useful